2010
DOI: 10.1111/j.1365-2125.2010.03679.x
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin dosing assessment in intensive care unit patients based on a population pharmacokinetic/pharmacodynamic simulation

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Despite the frequent use of vancomycin in intensive care unit (ICU) patients, few studies aimed at characterizing vancomycin population pharmacokinetics have been performed in this critical population. • Population pharmacokinetics coupled with pharmacodynamic analysis, in order to optimize drug exposure and hence antibacterial effectiveness, has been little applied in these specific patients. WHAT THIS STUDY ADDS • Our population model characterized the pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 44 publications
(64 reference statements)
4
85
2
7
Order By: Relevance
“…In our population of very elderly hospitalized patients, creatinine clearance was found to be associated with the vancomycin elimination rate constant, and body weight was associated with the volume of the central compartment. Apart from this relationship between creatinine clearance and elimination rate constant, we did not find any other significant relationships between patient age and pharmacokinetic parameters, contrary to studies carried out in young children (22) or in adult intensive care unit patients (28). This could be explained by the existence of immature processes in young children, such as kidney function (22), and by a larger range of ages in the population studied by Revilla et al (28), in which patients were between 18 and 85 years.…”
Section: Discussioncontrasting
confidence: 55%
“…In our population of very elderly hospitalized patients, creatinine clearance was found to be associated with the vancomycin elimination rate constant, and body weight was associated with the volume of the central compartment. Apart from this relationship between creatinine clearance and elimination rate constant, we did not find any other significant relationships between patient age and pharmacokinetic parameters, contrary to studies carried out in young children (22) or in adult intensive care unit patients (28). This could be explained by the existence of immature processes in young children, such as kidney function (22), and by a larger range of ages in the population studied by Revilla et al (28), in which patients were between 18 and 85 years.…”
Section: Discussioncontrasting
confidence: 55%
“…The present results show that, in critically ill patients with normal renal function, a daily dose of 3000 mg of vancomycin in continuous infusion (following a loading dose) is required to achieve a plateau concentration of 25 mg/L. Only recently, Revilla et al [13] found, based on a M a n u s c r i p t 7 population model using Monte Carlo simulations, that a dose of 3 g vancomycin was needed for an adequate response in patients with S. aureus infections.…”
Section: Discussionmentioning
confidence: 98%
“…Estimation of such parameters will be derived from input of data on patient characteristics, MIC of the pathogen and a priori population PK indices. The latter have been developed for children and adults with ESKD, malignancy, critical illness and neutropenia Haeseker et al 2016;Camaione et al 2013;Abdel Hadi et al 2015;Revilla et al 2010].…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%